Lessons From the Edge: A learning curve for all - Barrett-Carrier, Lynne (Apprendre et enseigner aujourd’hui, 2022)
When schools across this province were ordered to close on March 13, 2020, due to the Covid-19 pandemic, classroom teachers could never have imagined the profound repercussions of this decision and the colossal impact this would have on both teachers and students across Quebec. Teachers scrambled to upgrade their technology skills as school boards quickly mobilized to provide much-needed technical support and hardware for teachers, students, and parents/guardians. More than ever, home and school needed to be connected. In a quick response to the urgent need to provide a continued opportunity for learning, the virtual classroom soon took centre stage.In January 2022, a couple of months before the pandemic sent us into lockdown, I became a McGill Field Supervisor for the Faculty of Education as my career as a secondary school/ adult education ELA teacher would soon come to a close. I had planned to retire that June after teaching for 42 years at the English Montreal School Board. In my three final months at the EMSB, I designed, with a colleague, an online Secondary 5 ELA course, and became very well-acquainted with Microsoft Teams and all it had to offer. The course was both solid and engaging, affording the students the opportunity to work on their own, in small groups in break out rooms, and co-operatively as a whole class. Students were expected to participate and were held accountable for their contributions to the learning experience.